Performance of Telenomus remus (Hymenoptera: Scelionidae), an egg parasitoid of Spodoptera frugiperda (Lepidoptera: Noctuidae), under different temperature regimes - Suma, N M; Srinivasan , T; Marimuthu , M; Pagalahalli , SS; Premalatha , K; Raghu, R; Srinivasan, MR; Ramya, AR (Plant Science Today, 2025)
Maize fall armyworm, Spodoptera frugiperda (J.E. Smith) (Noctuidae: Lepidoptera), is a highly destructive and invasive pest of maize, causing havoc in major maize growing states of the country since 2018. Integrated Pest Management (IPM) strategies are being advocated to farmers for the containment of the pest. Among the various IPM components, biological control using the egg parasitoid, Telenomus remus (Nixon) (Scelionidae: Hymenoptera) could be considered a promising strategy, as the pest can be managed at a much earlier stage. This study evaluated the influence of five temperature regimes (20, 25, 30, 35 and 40 °C) on the developmental and reproductive performance of T. remus. Results indicated that 25-30 °C was optimal, with the highest parasitism (80.70 ± 5.29 eggs/female/24 hrs) and adult emergence (99.51 ± 0.20 %) at 25 °C. Developmental time decreased with increase in temperature, ranging from 8.60 days (35 °C) to 21.95 days (20 °C). Peak fecundity (122.7 ± 3.56 eggs/female) and intrinsic rate of increase (rm = 0.479) occurred at 30 °C. No reproduction occurred at 40 °C. These findings underscore the critical role of temperature in optimizing T. remus performance, aiding its effective integration into biological control programs against S. frugiperda.